Implementasi Kepatuhan Syariah terhadap Produk-produk Baitul Mal Wat Tamwil An-Nahdliyyin Gunung Lerang - Mastura, Emy; Farida, Ida (Islamic Banking and Finance, 2024)
The objectives of this research are (1) To find out the types of products offered by BMT Nahdliyin Gunung Lerang, (2) To find out the implementation of sharia compliance in BMT Nahdliyin Gunung Lerang products. This research uses a qualitative approach, the data collection techniques used are observation and interviews. The subjects of this research are the administrators and members of BMT Nahdliyin Gunung Lerang, the research objects are the products at BMT Nahdliyin Gunung Lerang. The data analysis techniques in this research are data collection, data reduction, data presentation and drawing conclusions. The results of this research show that: (1) The types of products offered by BMT Nahdliyin Gunung Lerang are, Baitul Ma'al Products: Santri Savings, Short Term Financing and Long Term Financing. Then Baitul Tamwil Products: Livestock and Agriculture, (2) Implementation of sharia compliance for BMT Nahdliyin Gunung Lerang products that meet sharia compliance. Based on the first product, namely student savings using a wadiah or deposit agreement which is in accordance with sharia principles. Then short-term and long-term financing products use a qardh contract which refers to providing loans without any additional rewards or benefits. Furthermore, livestock products use a musyarakah agreement, namely cooperation and joint participation between BMT Nahdliyin and investors. Then agricultural products consisting of chilies, eggplant, bananas and sweet potatoes use a mudharabah contract, which is a form of cooperation between capital owners (shahibul maal) and capital managers (mudharib) in certain projects.